#TITLE_ALTERNATIVE# - BRAMONO (NIM 13700033), SETO
Dynamic dent resistance of impacted materials is defined as the elastically absorbed energy. However, its value can be determined by the ratio between the impacted energy and the volume of dent surface. The dynamic dent resistant testing were performed at the strain rate of 102-104s-1. Aluminum and steel, as popularly applied as structural automotive materials, were selected for the dynamic dent test. The aluminum and steel specimens were manufactured and resulted in the same dimensions and mechanical properties, except it’s modulus of elasticity. It has been readily observed that damaged surface of steel specimens were more concentrate than that of aluminum specimens, at all impact velocity. This research also support that the lower the modulus elasticity of the materials, the higher the dent resistant will be.